Social differences in Neolithic/Bronze Age Myanmar: 87Sr/86Sr in skeletal remains from Oakaie 1 and Nyaung'gan. (October 2018) - Bentley, R. Alexander; Willis, Anna; Pradier, Baptiste; Kyaw, Aung Aung; Win, Tin Tin; Brandon, Alan D.; Pryce, T.O.
Abstract: Here we begin to investigate prehistoric kinship and social differentiation in ancient Myanmar, through analyses of strontium isotopes in human tooth samples from excavated skeletal remains of 18 individuals from the archaeological sites of Oakaie 1 and Nyaung'gan, in Sagaing Division, central Myanmar. The archaeological deposits at these sites span the Late Neolithic and Early Bronze Age (approximately 12th to 8th c. BCE). These isotopic data are interpreted in association with bioarchaeological, material culture and stratigraphic data. These preliminary results suggest a differentiation in mean strontium signatures between the sites, which are <3 km apart, but with sex-based patterns within the sites. This indicates kinship was a strong organizing principle, with little long-distance migration, despite apparently considerable long-distance exchange networks active by the early Bronze Age in Myanmar. Highlights: We present the first strontium isotopes results from human teeth from prehistoric Myanmar. We find distinct strontium isotope signatures from two sites only a few km apart. Sr isotope signature for men and women from Oakaie also differ. Kinship was a strong organizing principle, with little long-distance migration. The data contribute to a larger investigation of the origins of complex society in Myanmar.